(untitled) (Oxford, 2006)
A clear structural syllabus set in the context of everyday business functions. Accompanying video: Meeting Objectives
Keywords: English language,English language,Tiếng Anh thực hành,Tiếng Anh thực hành; Business English,Tiếng Anh trong kinh doanh